Academic and educational development research, evaluation and changing practice in higher education - Macdonald, Ranald 1952-; Wisdom, James (Staff and educational development series, 2002)
With much emphasis on change and developing best practice in higher education, it is essential that those involved in developing, researching or implementing approaches to teaching, learning or management are aware of the experiences of others.